2020
DOI: 10.1002/cam4.3303
|View full text |Cite
|
Sign up to set email alerts
|

Exosome‐transmitted linc00852 associated with receptor tyrosine kinase AXL dysregulates the proliferation and invasion of osteosarcoma

Abstract: Background Receptor tyrosine kinase AXL has been found to be highly expressed in osteosarcoma and positively associated with poor prognosis. There are tumor groups with high or low AXL expression, which had different capabilities of invading vessels and forming distal metastases. Exosome‐transmitted lncRNA may be transferred intercellularly to promote tumor cells’ proliferation and invasion. Methods Exosomes were detected by electron microscopy, particle size analysis, and western blotting. High‐throughput seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…For example, Zhao et al (2019) found that BMSCs‐derived Exos encapsulate PVT1 and transport it into OS cells, and the transported PVT1 facilitates tumors to grow and metastasize via repressing ubiquitination and elevating ETS transcription factor ERG (ERG) expression in OS cells. Li et al (2020) confirmed that the AXL‐exo‐linc00852‐AXL positive feedback loop might exist between donor cells and receiver cells.…”
Section: Exo‐ncrnas In Osmentioning
confidence: 96%
“…For example, Zhao et al (2019) found that BMSCs‐derived Exos encapsulate PVT1 and transport it into OS cells, and the transported PVT1 facilitates tumors to grow and metastasize via repressing ubiquitination and elevating ETS transcription factor ERG (ERG) expression in OS cells. Li et al (2020) confirmed that the AXL‐exo‐linc00852‐AXL positive feedback loop might exist between donor cells and receiver cells.…”
Section: Exo‐ncrnas In Osmentioning
confidence: 96%
“…Li et al demonstrated that osteosarcoma could releasing exosomes that contain linc00852 and there is a positive feedback regulation loop between AXL and exosome derived linc00852. As a result, the growth, invasion and metastasis of osteosarcoma cells with low AXL expression were able to be promoted by osteosarcoma cells with high AXL expression ( Figure 2 ; Li Q. et al, 2020 ). Zhang et al reported that macrophages derived exosomal lncRNA LIFR-AS1 via the miR-29a/NFIA axis promoted osteosarcoma cell proliferation and invasion ( Zhang H. et al, 2021 ).…”
Section: The Functions Of Cargoes Derived From Exosomes In Osteosarcomamentioning
confidence: 97%
“…Meanwhile, a few linc00852 play a role as ceRNA for miR-7-5p to increase expression of AXL in cytoplasm. Reprinted from Li Q. et al (2020) .…”
Section: The Functions Of Cargoes Derived From Exosomes In Osteosarcomamentioning
confidence: 99%
“…In osteosarcoma miR-7 influences IGF1R , and in paediatric rhabdomyosarcomas targets SLC25A37 and TIMM50 , two mitochondrial proteins, important for the induction of cell death [ 79 , 111 ]. In osteosarcomas, miR-7 is supposed to be a regulating link between Linc00852 lncRNA, and AXL, a tyrosine kinase involved in tumor growth [ 169 ].…”
Section: Mir-7 Roles In Mesenchymal Tissue and Tumoursmentioning
confidence: 99%